Development of Motion Manipulator System for a Generic Aircraft Flight Dynamic Simulator - Kurniawan Asalani, Yusuf; Adhy Sasongko, Rianto; Arifianto, Ony (International Journal of Engineering and Technology, 2018)
The purpose of this development program is to apply some prior studies about hexapod manipulator for designing aircraft simulator motion platform in terms of acceleration cue. Acceleration would represent human perception to describe a motion. By giving acceleration cues in a simulator, the operator would obtain similar sensation corresponding to real phenomenon/condition. Iteration process is used to collect relations between hexapod manipulator parameters, platform size and actuator position, and manipulator performances describing as manipulator displacement and acceleration range. Its kinematics and dynamics are modelled by using Newton-Euler approach and validated by using SimScape feature provided in MATLAB/Simulink. Hereafter, actuation control scheme would be implemented in order to convey manipulator from a conceptual world into real world based on its dynamics. As part of this development, constructing hexapod manipulator numerical model becomes the main objective of this current research.Â Â